Pentingnya Komitmen Bisnis Independent Business Owner Pada MLM Oriflame - Martin Luter (LPPM Universitas HKBP Nommensen, 2020)
People’s interest in doing business is getting higher, coupled with the advancement of technology, it is increasingly helping many people to introduce their products. There are many ways that someone can do to generate income, one of which is by doing the Oriflame MLM business. To develop their business network, IBOs must be highly committed. The results of the respondents’ answers regarding business commitment show that a well-committed IBO will produce a good business network, as evidenced by the achievement of better bonuses.